BENTUK PERTUNJUKAN KESENIAN LINTAU PADA MASYARAKAT DELI SERDANG - sandra juliana samosir (Universitas Negeri Medan, 2014)
The aim of this study is to describe the history of Lintau’s art and art formin Deli Serdang society. Theoretical frameworks used in this study are theories related to the topic of discussion, such as the theory of forms, the meaning in history, as well as the conceptual framework as a translation of the concerns expressed in it.The method that’s used in this study is descriptive qualitative method. Collecting data was done by field observations, documentation, data collection and interviews. As for the sample in this study is an artist ,performer of Lintau, and the people who know about Linta’s art.The result of this study indicates that the Lintau’s art is a martial art, based on the history that Silat Lintau taken by Sheikh Batu Mandi, from village Lintau Minangkabau specifically in Tanah Datar.Silat (Silek) of Lintau is a technique or a martial art, owned by the people, that have been passed through generation. Silat Lintau was formerly performed only in the palace by certain people, due to the stages before and after learning and performing it. Currently Silat Lintau hasn’t prioritized those stages, and has become a folk performances, known as Lintau Art. The form of Lintau’s Art performance composed of a wide-range of motion which consists of opening respectful posture, stance consists of four (4) types of punches and evasive, four (4) types of punches, which stems from mashed, simbor, tetak, and beak. Furthermore, the last step of the board and respectful cover. Keywords: Pertunjukan Kesenian Lintau.